Transradial intra-aortic catheter looping in the angioplasty of severe intracranial symptomatic arteriosclerotic diseases - Xu, Gang-Qin; Xia, Jin-Chao; Cai, Dong-Yang; Yang, Bo-Wen; Zhao, Tong-Yuan; Xue, Jiang-Yu; Wang, Zi-Liang; Li, Tian-Xiao; Gao, Bu-Lang (Frontiers in Neurology, 2023)
PPurpose: To investigate the effect and feasibility of intra-aortic catheter looping via the transradial access in angioplasty for symptomatic intracranial severe (>70%) atherosclerotic stenosis or occlusion of large arteries (SISOLA). Materials and methods: Patients with SISOLA treated with transradial endovascular angioplasty using the intra-aortic catheter looping technique were retrospectively enrolled. The clinical data and treatment outcomes were analyzed. Results: Fifteen patients aged 48-71 years were enrolled. Left vertebrobasilar artery occlusion was present in 1 (6.7%) patient, severe left middle cerebral artery stenosis in 7 (46.7%), severe left internal carotid artery (ICA) stenosis of the ophthalmic segment in 4 (26.7%), severe left ICA stenosis of the cavernous segment in 2 (13.3%), and severe right middle cerebral artery stenosis in 2 (13.3%). The arterial stenosis ranged 70%-92% (mean 86%) before stenting. Looping of a guiding catheter was successful in the ascending aorta via the transradial access for angioplasty in all patients (100%). The vertebral artery intracranial segment occlusion was successfully recanalized while the severe stenosis in the other 14 patients was all successfully eliminated. After endovascular recanalization, the residual stenosis was reduced to 12%-26% (median 18%). No puncture-related complications or surgical-related neurological complications occurred in these patients. In follow-up angiography in 10 (66.7%) patients 6-25 months later, no instent restenosis was detected. Conclusion: Intra-aortic guiding catheter looping via the transradial access for endovascular angioplasty of severe symptomatic intracranial atherosclerotic stenosis or occlusion of large arteries is technically safe, feasible and effective in case of difficulty or impossibility in the transfemoral artery approach.